Spatial trends in United States tornado frequency. Issue 1 (December 2018) - Gensini, Vittorio; Brooks, Harold
Abstract Severe thunderstorms accompanied by tornadoes, hail, and damaging winds cause an average of 5.4 billion dollars of damage each year across the United States, and 10 billion-dollar events are no longer uncommon. This overall economic and casualty risk—with over 600 severe thunderstorm related deaths in 2011—has prompted public and scientific inquiries about the impact of climate change on tornadoes. We show that national annual frequencies of tornado reports have remained relatively constant, but significant spatially-varying temporal trends in tornado frequency have occurred since 1979. Negative tendencies of tornado occurrence have been noted in portions of the central and southern Great Plains, while robust positive trends have been documented in portions of the Midwest and Southeast United States. In addition, the significant tornado parameter is used as an environmental covariate to increase confidence in the tornado report results. ATMOSPHERIC HAZARDS: understanding tornado trends While the number of tornadoes has remained fairly static in the United States over the past 40 years, strong geographic contrasts are apparent. Tornadoes have the potential to cause severe damage, yet understanding their changes in time—particularly the impact of anthropogenic warming—has been hampered by sparse observations. Vittorio Gensini and Harold Brooks, from Northern Illinois University and the National Severe Storms Laboratory, respectively, therefore use a proxy of tornado activity—the significant tornado parameter, STP—to investigate regional trends since 1979. Tornado counts have increased in the Southeast, Midwest, and Northeast, as represented by a robust upward trend in the STP. In the southern Great Plains, by contrast, negative trends are apparent. These regional differences emphasise the need to consider geographic variability when assessing projected shifts in tornado hazards.